Dorothy Hodgkin and the discovery of the structure of insulin - VALDÉS, JUAN NÚÑEZ (International Journal of Multidisciplinary Research and Studies, 2024)
Despite being Nobel Prize winner, the figure of Dorothy Hodgkin is not well known beyond researchers in Biology, Chemistry and Pharmacy, and yet her discoveries, which made she worthy of being awarded the Nobel Prize, make her equally worthy of being recognized by all society. The objective of this article is to publicize her figure and place her as references for women who have achieved important milestones in the performance of their professions and whose research have been enormously useful for society. The methodology followed has been the search for information in all types of sources, both bibliographic and digital, on Dorothy Hodgkin with the proposal of showing her most notable discoveries and remarking the service she has provided to society.